The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.tifs.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

(Bio)chemical reactions during high pressure/high temperature processing affect safety and quality of plant-based foods

Abstract: In recent years, the range of equipment and applications for high pressure pasteurization has gradually increased on the European market. Sterilization under conditions of elevated pressures is in the pipeline, albeit at the research level. Knowledge on the effect of high pressure/high temperature processing on food safety and quality attributes is still too limited. This review discusses recent progress made in understanding the impact of high pressure/high temperature processing on food safety and quality at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 74 publications
3
30
1
Order By: Relevance
“…According to Balny et al, [25] HP can induce hydration changes which in turn may cause protein structural changes and denaturation, and this phenomenon may explain why proteins in a solution are more unstable to HP than those in the dry state. However, in contrast to those studies, our current study and that of Van der Plancken et al [4] showed a different HP effect -that is, peanut allergens prepared in solutions were stable to HP rather than undergoing structural changes. Figure 3 shows the SDS-PAGE protein profiles of the untreated, PPO-, HP300/PPO-and HP500/PPO-treated peanut extracts at 3 and 10 min.…”
Section: Inhibition Elisa For Ige Bindingcontrasting
confidence: 99%
See 3 more Smart Citations
“…According to Balny et al, [25] HP can induce hydration changes which in turn may cause protein structural changes and denaturation, and this phenomenon may explain why proteins in a solution are more unstable to HP than those in the dry state. However, in contrast to those studies, our current study and that of Van der Plancken et al [4] showed a different HP effect -that is, peanut allergens prepared in solutions were stable to HP rather than undergoing structural changes. Figure 3 shows the SDS-PAGE protein profiles of the untreated, PPO-, HP300/PPO-and HP500/PPO-treated peanut extracts at 3 and 10 min.…”
Section: Inhibition Elisa For Ige Bindingcontrasting
confidence: 99%
“…Our data are in agreement with the finding of Van der Plancken et al, [4] in which purified peanut allergens (Ara h 2 and Ara h 6) were found to be stable to HP between 150 and 800 MPa (10 min), and their structures remained unchanged even during HP treatment at 80 • C. By contrast, allergens from apples treated with HP at 80 • C exhibited structural changes and a reduction in immunoreactivity. [4,6] The high stability of peanut allergens to HP as shown in this study and that of Van der Plancken et al [4] is unusual because HP has previously been shown to induce protein denaturation, dissociation, or aggregation [8,15] and as a result, the HP-treated proteins are more easily digested and have a lower immunoreactivity. Also, HP can destabilize hydrophobic interactions, [24] which usually play a major role in the stabilization of protein tertiary structure.…”
Section: Inhibition Elisa For Ige Bindingsupporting
confidence: 93%
See 2 more Smart Citations
“…Volume increased with the addition of enzymes and this was observed at all pressure levels. This might indicate a decrease in water absorption due to the activity of exogenous pectinases resulting in a polymer network breakdown (Van der Plancken et al, 2012). Further experiments should be carried out to confirm this hypothesis.…”
Section: Liquid Liberated Volume Wet Solid Weight and Ph Changesmentioning
confidence: 94%